Sustainability standards and certification: towards sustainable palm oil in Indonesia? - Clara Brandi; Tobias Cabani; Christoph Hosang; Sonja Schirmbeck; Lotte Westermann; Hannah Wiese (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Palm oil production is currently the focus of much contentious debate. On the one hand, palm oil production has a substantial, positive (socio-) economic impact in countries which produce it, like Indonesia, and is a powerful engine of rural development. On the other hand, palm oil production has a severe negative impact regarding ecological and social sustainability. This is due above all to its large carbon footprint, reduced biodiversity, and its potential for triggering land rights conflicts. The growing world demand for and rising production of palm oil underlines the relevance of sustainability questions in this regard. Sustainability concerns have spurred numerous efforts to introduce standards and certification schemes for sustainable palm oil production. In Indonesia, two of these standards are particularly relevant: ISPO (Indonesian Sustainable Palm Oil) and RSPO (Roundtable on Sustainable Palm Oil). This Briefing Paper focuses on the question of whether sustainability standards like RSPO can represent an effective tool for minimising the negative ecological impact of palm oil cultivation. We argue that this depends on a number of factors, including: (i) the inclusion of smallholders as a highly important group of producers in the Indonesian palm oil industry, (ii) the strictness of the standard's Principles and Criteria (P&C), (iii) their adequate implementation and control, (iv) a suitable political and economic framework for smallholder certification, especially regarding good governance and domestic and international demand for certified, sustainable palm oil (CSPO). Against this background, practical steps to enhance the effectiveness of sustainability standards include: Supporting smallholder certification projects with a strong ecological component Balancing a trade-off between strict and easy- toreach standards Balancing a trade-off between socioeconomic and ecological goals Choosing reputable certification bodies and reliable project partners Increasing incentives and/or outside pressure to stay certified Improving the coherence of land use planning, laws and regulations Fighting corruption and strengthening law enforcement
Keywords: 330; Handel und Investitionen; Landwirtschaft und ländliche Entwicklung; Umwelt; Ökosysteme und Ressourcen